(untitled) (Research, Society and Development, 2022)
The aim was to describe the behavioral repertoire and the preference for different toys of rabbits housed in collective pens with or without environmental enrichment. For this, 24 New Zealand White rabbits with 58 ± 3 days of age were used. Two treatments were adopted: with environmental enrichment and without environmental enrichment. The enrichment consisted of placing toys inside the pens, namely: plastic flooring, sisal rope, wooden blocks and chains. The behavioral repertoire was determined from footage taken during 24 hours over three alternate days. The behavior was recorded every 10 minutes. Chi-Square and Kruskal-Wallis tests were used at 5% significance. The animals housed in enriched pens showed a higher frequency of exploratory behavior, while animals in non-enriched pens had a higher occurrence of social interaction and grooming, both performed more frequently during the night and morning. The Grooming was more frequent during the night period. The rabbits interacted with all the toys at night, and the sisal rope was the one that also promoted interaction during the morning. The plastic flooring was most often fetched in the afternoon, while the rabbits slept. The inclusion of environmental enrichment in the creation of rabbits housed in collective pens increased the exploratory behavior of the animals during the night, with the sisal rope being the preferred toy, having been sought throughout the night and during the morning.